Hubungan Kekuatan Otot Lengan, Panjang Lengan dan Koordinasi Mata-Tangan terhadap Hasil Servis Atas Bola Voli pada Siswa Ekstrakurikuler SMP Islam Fatahillah Kota Sukabumi Tahun Pelajaran 2023/2024 - Muhamad Yusup; Ahmad Alwi Nurudin; Bachtiar Bachtiar (Pusat Riset dan Inovasi Nasional, 2024)
The aim of this research is to determine whether there is a relationship between arm muscle strength, arm length and hand-eye coordination on the results of volleyball serves in extracurricular students at Fatahillah Middle School, Sukabumi City, academic year 2023/2024. The development of science and innovation, sports in Indonesia, especially volleyball, is progressing very rapidly. Therefore, in this game you are required to have a tall physique, strong muscles and reliable movement coordination in carrying out all the movements in the volleyball game with sports development as part of efforts to improve spiritual and physical health. The method used is a survey method with tests and measurements. The sampling technique was a total sampling of 17 students. The research instrument uses an Anthropometer as a tool to measure arm length. The data analysis technique used is standard deviation, looking for normality and homogeneity values ​​and then looking for paired T test values. The results of this research are that there is a significant effect, with the paired sample t test, muscle strength and eye-eye coordination obtained a significance value of 0.000. relationship between arm muscle strength, arm length and hand-eye coordination on volleyball service results among extracurricular students at Fatahillah Middle School, Sukabumi City.